Influence of Store Atmosphere, Promotion Applicatian and Product Display Towards Consumer Satisfaction Tomoro Coffee Bengkulu City - Pratiwi, Rindi Intan; Yanti, Rina Trisna; Tambunan, Dennis Rydarto (BIMA Journal (Business, Management, & Accounting Journal), 2024)
Purpose:Â This study aims to examine the impact of store atmosphere, promotion application, and product display on consumer satisfaction at Tomoro Coffee in Bengkulu City.Â Methodology:Â A quantitative approach was employed using questionnaires as the primary data collection tool. The study sampled 150 consumers of Tomoro Coffee in Bengkulu City.Â Results: The multiple linear regression analysis produced the equation Y = 1.454 + 0.325(Xâ‚) + 0.240(Xâ‚‚) + 0.411(Xâ‚ƒ) + 2.837, showing a positive relationship between the three variables and consumer satisfaction. The determination coefficient (RÂ²) of 0.640 indicates that 64% of consumer satisfaction is influenced by these factors, while 36% is attributed to other unexamined variables.Â Findings: The combined influence of store atmosphere, promotion application, and product display significantly affects consumer satisfaction, supported by an F value of 86.424 > 2.67 and a significance level of 0.000 < 0.05.Â Originality: This study provides insights into consumer behavior within the growing coffee shop culture in Bengkulu.Â Novelty: It highlights the importance of these factors in shaping customer satisfaction, specifically in a modern coffee shop context.Â Conclusion:Â Enhancing store atmosphere, promotions, and product displays can significantly boost customer satisfaction.Â Type of Paper:Â Empirical researchÂ paperÂ .Â